There's a lot going on in this problem, but I think I know how to solve it. So let's first address the fact that opposite angles are equal.
Let's also address the fact that (x + 6) + (3x - 4) add up to equal 90. So with that information, we can write a problem.
x + 6 + 3x - 4 = 90
Add the x's.
4x + 6 - 4 = 90
Combine the 6 and 4.
4x + 2 = 90
Subtract the two on both sides.
4x = 88
Finally, divide by 4.
x = 22
But by no means are we done yet. We still have to find out the entire angle MFE's measure, so we'll substitute 22, our new x value, into the equation for MFE - (x + 6)
22 + 6 is the new equation.
22 + 6 = 28
Angle MFE is 28°. I took the liberty of solving for the other angle, too, so I could check the answer. And as of my checking, this answer is correct because
62 + 28 = 90
I hope this answers your question.
-Toremi